2002
DOI: 10.1562/0031-8655(2002)075<0140:ivaive>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro and In Vivo Efficacy of Photofrin® and Pheophorbide a, a Bacteriochlorin, in Photodynamic Therapy of Colonic Cancer Cells¶

Abstract: This study was designed to investigate the efficacy of photodynamic therapy (PDT) in treating colonic cancer in a preclinical study. Photofrin, a porphyrin mixture, and pheophorbide a (Ph a), a bacteriochlorin, were tested on HT29 human colonic tumor cells in culture and xenografted into athymic mice. Their pharmacokinetics were investigated in vitro, and the PDT efficacy at increasing concentrations was determined with proliferative, cytotoxic and apoptotic assessments. The in vivo distribution and pharmacoki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
60
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(63 citation statements)
references
References 40 publications
3
60
0
Order By: Relevance
“…Pba was shown to cause mitochondria-dependent apoptosis in cultured cancer cells (Tang et al, 2009). In vivo animal models also demonstrated that Pba impedes tumor growth in colon carcinoma and hepatoma xenograft models (Hajri et al, 2002;Li et al, 2007). However, the development of PDT resistance has been displayed: colon cancer cells repeatedly exposed to PDT agents developed resistance to PDT (Singh et al, 2001).…”
Section: Orgmentioning
confidence: 99%
“…Pba was shown to cause mitochondria-dependent apoptosis in cultured cancer cells (Tang et al, 2009). In vivo animal models also demonstrated that Pba impedes tumor growth in colon carcinoma and hepatoma xenograft models (Hajri et al, 2002;Li et al, 2007). However, the development of PDT resistance has been displayed: colon cancer cells repeatedly exposed to PDT agents developed resistance to PDT (Singh et al, 2001).…”
Section: Orgmentioning
confidence: 99%
“…Several in vivo animal studies have supported the efficacy of Pba-PDT in preventing tumorigenesis. For instance, a liposomal preparation of Pba-PDT delayed tumor growth in a colon carcinoma HT29 xenograft [19]. Intravenous administration of 0.3 mg/kg Pba followed by light irradiation significantly inhibited tumor growth in nude mice harboring a human hepatoma xenograft [11].…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation of DPBF-isopropanol solution in the absence of photosensitizers was also carried out as negative control. The singlet oxygen generation rate for each phthalocyanine was determined relative to Pha which has a singlet oxygen quantum yield of 0.52 in alcohol [24].…”
Section: Methodsmentioning
confidence: 99%